Fe3O4 Nanoparticles Loaded on Lignin Nanoparticles Applied as a Peroxidase Mimic for the Sensitively Colorimetric Detection of H2O2 - Qingtong Zhang; Mingfu Li; Chenyan Guo; Zhuan Jia; Guangcong Wan; Shuangfei Wang; Douyong Min (Nanomaterials, 2019)
Lignin is the second largest naturally renewable resource and is primarily a by-product of the pulp and paper industry; however, its inefficient use presents a challenge. In this work, Fe3O4 nanoparticles loaded on lignin nanoparticles (Fe3O4@LNPs) were prepared by the self-assembly method and it possessed an enhanced peroxidase-like activity. Fe3O4@LNPs catalyzed the oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB) in the presence of H2O2 to generate a blue color, was observable by the naked eye. Under the optimal conditions, Fe3O4@LNPs showed the ability of sensitive colorimetric detection of H2O2within a range of 5⁻100 μM and the limit of detection was 2 μM. The high catalytic activity of Fe3O4@LNPs allows its prospective use in a wide variety of applications, including clinical diagnosis, food safety, and environmental monitoring.